Application of AI Technology in Drug Discovery and Vaccine Development in the Pharmaceutical Sector and the Impact on the Business Sector and Employment in the Pharmaceutical Sector - Ependi; Juniarti; Nuriana (PT FORMOSA CENDEKIA GLOBAL, 2023)
The application of AI technology in drug discovery and vaccine development in the pharmaceutical sector can have a positive impact on the business sector and employment opportunities in the pharmaceutical sector. However, the application of AI technology in the pharmaceutical sector also has several challenges, such as limited experts who have technical skills and understanding of the scientific side of a process. In order to maximize the potential impact of AI in pharma, appropriate investment in research and development is required, as well as the implementation of strong regulations and ethical standards. With this understanding, we can better appreciate the role and value of AI in pharma and global health. In journals and articles discussing the application of AI technology in the pharmaceutical sector, research methods used include the use of learning machine algorithms, vaccine development, ethical challenges and considerations, as well as investment and adoption.